District nutrition profiles, a compiled set of indicators that can be used to dialogue with stakeholders about where to focus efforts on addressing undernutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
All profiles are posted online and disseminated to stakeholders. There is evidence of uptake by stakeholders in India, but it does not meet the standards for this 2019 report. We note that the profiles have been used for district diagnostic exercises during short nutrition workshops and district-level trainings.